The Effect of Urea and NPK Fertilizer Usage on Farmers Receiving Fertilizer Subsidies - Januarisky, Hanna Aditya; Syaukat, Yusman; Rifin, Amzul (Agro Bali : Agricultural Journal, 2025)
The implementation of subsidized fertilizer policies has been implemented in Indonesia since the 1970s until now. The government's policy of spending a budget to subsidize fertilizer prices has yet to be able to encourage increased productivity of agricultural products. This indicates that the government's efforts in input price subsidies must be more effective in stabilizing rice productivity in terms of the subsidized fertilizer policy expenditure budget. The objectives of this research are 1) to analyze the effectiveness of subsidized fertilizer distribution and 2) to analyze the effect of using urea and NPK fertilizers on farmers who receive fertilizer subsidies for rice production. This research uses primary data by directly interviewing respondent farmers in Kertajati District and Majalengka District, Majalengka Regency. The assessment of the effectiveness of the subsidized fertilizer policy can be measured using six appropriate indicators, namely the exact type, exact quantity, exact price, exact place, exact time, and exact quality. The effect of urea and NPK fertilizers was analyzed using the Cobb-Douglas production function with the ordinary least squares method. This research found that the effectiveness of subsidized fertilizer distribution in Majalengka District has a percentage level of effectiveness above 74.2% (quite effective). Analysis of the effect of using urea and NPK fertilizer shows that the independent variables that positively and significantly influence rice production are seeds, use of urea fertilizer, and labor. Different things happen to the NPK fertilizer, and using a mixture of subsidized and non-subsidized fertilizers has no significant effect on rice production.